Derivational and Inflectional Morphemes on Joko Widodo’s Speech for English Education - Aryanika, Septa -; Henisah, Ratih; Kurniawati, Dewi; Susanto, Is (English Education: Jurnal Tadris Bahasa Inggris, 2021)
This study aims to determine the frequency and process of derivational and inflectional morphemes in Joko Widodo's speech at the Asian Pacific Economic Cooperation summit. The study used descriptive qualitative analysis methods. The data were analyzed using Fromkin's principle. The data analysis yielded 133 terms made up of derivational and inflectional morphemes. Derivational morphemes accounted for 50.37 percent of all occurrences in this study, while inflectional morphemes accounted for 49.63 percent. The researchers discovered several derivation processes that modify grammatical classes while remaining unchanged, such as noun form, adjective form, verb form, adverb form, adjective form, noun to noun, and adjective to adjective. In this study, five types of Inflectional morphemes were found: -s (plural and third-person singular), -ing (progressive), -ed (past tense), and -er (comparative).  Morphemes are an important feature of language so it is important for students to learn in school, especially for language learners. Morphological awareness, which we describe as a basic understanding of the morphemic structure of words, is required of the learner. Finally, the implications of this research will be an inspiration for further research in morphological processing, especially regarding derivational and inflectional morphemes.